Nonlinear Association Between Serum Uric Acid and Femoral Neck Bone Mineral Density in Male Patients with Metabolic Dysfunction-Associated Fatty Liver Disease - Tan J; Wang L; Li H; Wang H; Yang X (Diabetes, Metabolic Syndrome and Obesity)
Juan Tan,1,* Lin Wang,1,* Hong Li,2 Honggang Wang,3 Xiaozhong Yang3 1Department of General Practice, The Affiliated Huai ‘an No. 1 People’s Hospital of Nanjing Medical University, Huai’an, Jiangsu, People’s Republic of China; 2Department of Health Management Center, The Affiliated Huai ‘an No. 1 People’s Hospital of Nanjing Medical University, Huai’an, Jiangsu, People’s Republic of China; 3Department of Gastroenterology, The Affiliated Huai ‘an No. 1 People’s Hospital of Nanjing Medical University, Huai’an, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Honggang Wang; Xiaozhong Yang, Email hayy_wanghg@163.com; hayy_yxzh@163.comPurpose: To investigate the relationship between serum uric acid (SUA) levels and femoral neck bone mineral density (BMD) in patients with metabolic dysfunction-associated fatty liver disease (MAFLD).Patients and Methods: This cross-sectional study included 597 adult inpatients with type 2 diabetes mellitus and ultrasonography-confirmed fatty liver disease. Participants were stratified into tertiles based on femoral neck BMD. Gender-stratified linear regression analyses were performed to assess the relationship between SUA and femoral neck BMD. Nonlinear associations were explored using generalized additive models and two-piece linear regression.Results: No significant linear association was observed between SUA and femoral neck BMD in either gender (all P > 0.05). However, after adjusting for confounders, a nonlinear relationship was identified in male patients, with a threshold at 388 μmol/L. The effect sizes for SUA levels below and above this threshold were 0.001 (95% CI: 0.000 to 0.002, P = 0.008) and − 0.000 (95% CI: − 0.002 to 0.000, P = 0.117), respectively. No nonlinear relationship was observed in female patients.Conclusion: In male MAFLD patients, SUA levels exhibit a nonlinear relationship with femoral neck BMD, with a positive association observed between 300 μmol/L and 388 μmol/L. This relationship was not observed in female patients, suggesting gender-specific effects of SUA on bone health in MAFLD.Keywords: metabolic dysfunction-associated fatty liver disease, type 2 diabetes, serum uric acid, bone mineral density